Training the trainees: An evaluation exercise using the TLH and BSO model. (August 2013) - Saso, S.; Chatterjee, J.; Pai, P.; Farthing, A.; Ghaem-Maghami, S.
Abstract : Our aim was to evaluate surgical training in gynaecological oncology by assessing the time required by a trainee to complete a single laparoscopic gynaecologic-oncological operation. A total of 135 patients with a BMI < 40 kg/m 2, diagnosed with endometrial cancer, underwent a total laparoscopic hysterectomy and bilateral salpingo-oophorectomy (TLH and BSO). Patients in Group I ( n = 78) were operated on by a consultant gynaecological oncology surgeon and in Group II ( n = 57) by sub-specialist trainees (SSTs). The mean patient age and BMI was 63.5 years and 29.6 kg/m 2, respectively, in Group I and 64.5 years and 29.9 kg/m 2, respectively, in Group II. Median operating times for Groups I and II were 58 and 90 min, respectively ( p < 0.05). Furthermore, significant improvement was noted when comparing the average operating time between the first and second half of SST training. Even experienced gynaecological trainees take significantly longer to perform a reproducible laparoscopic operation. At the completion of training, an SST demonstrates improvement with respect to operation duration but is still not as fast as the trainer.